Interdisciplinary care of the periodontally compromised elderly patient (Bangladesh Journal of Medical Science, 2018)
Aim: Patients with a compromised periodontal condition, multiple missing teeth and pathological migration of tooth may require an interdisciplinarymanagement. To demonstrate that combined periodontic-surgical-restorative-prosthodontic-orthodontic treatment can achieve an improved periodontal condition, masticatory function, esthetics, and occlusion. Materials and Methods: This report describes the case of a 55-year-old woman with severely compromised periodontal tissues, multiple missing teeth, and malocclusion. An interdisciplinary, periodontic-surgicalrestorative- prosthodontic-orthodontic approach with strict plaque control during treatment was carried out.Results: Clinical examination revealeda well-functioning dentition, natural inappearance and in a harmonious occlusion and periodontalstate of health.The treatment outcomes, includingthe periodontal condition and the orthodontic treatment, were stable at the age of 60 years.Conclusion: Successful functional and esthetic results were achieved by an interdisciplinary management.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.161-168